Expectativas importadas: o trailer de cinema no mercado brasileiro - Jaber, Fernanda (Imagofagia, 2021)
Este texto investiga como a publicidade do trailer se encaixa na história da exibição de filmes do Brasil, um mercado dominado pelo produto fílmico importado. A metodologia utilizou uma ampla gama de fontes primárias de modo a articular como o trailer importado surge e se insere de forma maciça no contexto brasileiro. Palavras-chave: trailer de cinema, cinema brasileiro, publicidade de cinema, publicidade de Hollywood. Abstract: This article analyzes the role of trailers in the history of Brazilian cinema, a market dominated by Hollywood productions. The research methodology is based on information from a variety of primary sources (such as news reports, movie listings, readers’ letters, movie advertising and interviews), in order to articulate the context of the imported trailer format, its emergence, and its mass-scale insertion in Brazil. Key words: movie trailers, Brazilian film, film advertisement, Hollywood advertisement. Fecha de recepción: 01/06/2017 Fecha de aceptación: 31/08/2017